An mRNA vaccine against rabies provides strong and durable protection in mice - Li, Miao; Fang, Enyue; Wang, Yunpeng; Shi, Leitai; Li, Jia; Peng, Qinhua; Li, Xingxing; Zhao, Danhua; Liu, Xiaohui; Liu, Xinyu; Liu, Jingjing; Xu, Hongshan; et al. (Frontiers in Immunology, 2023)
Rabies is a serious public health problem worldwide for which an effective treatment method is lacking but can be prevented by vaccines. Current vaccines are produced in cell or egg cultures, which are both costly and time-consuming.Here, a non-replicating mRNA vaccine (RV021) encoding the rabies virus glycoprotein was developed in vitro, and its immunogenicity and protective efficacy against live virus was evaluated in mice. The results showed that a two-dose vaccination with 1 μg of RV021 at 7-day intervals induced a protective level of neutralizing antibody that was maintained for at least 260 days. RV021 induced a robust cellular immune response that was significantly superior to that of an inactivated vaccine. Two doses of 1 μg RV021 provided full protection against challenge with CVS of 30~60-fold lethal dose, 50%. Vaccine potency testing (according to the National Institutes of Health) in vivo revealed that the potency of RV021 at 15 μg/dose was 7.5 IU/dose, which is substantially higher than the standard for lot release of rabies vaccines for current human use. In conclusion, the mRNA vaccine RV021 induces a strong protective immune response in mice, providing a new and promising strategy for human rabies prevention and control.